Korelasi Tahanan Ujung Konus (qc) Dengan California Bearing Ratio (CBR) Untuk Tanah Di Banjarbaru: Correlation of cone tip resistance (qc) and California Bearing Ratio (CBR) for Soil in Banjarbaru - Cahyadi, Hendra (Media Ilmiah Teknik Sipil, 2019)
All this time, the score of CBR is calculated according to qc score. Generally, a planner usually refers to a graph / nomogram published in the literature book, but the graph/nomogram on the book may not probably able to apply in all areas, including Banjarbaru. In this particular research, it aimed to make the graph or equation between CBR and Cone tests in the cone area of 0.5 in2. Both tests used the same sample of water contents and density. The samples were taken in four areas in Banjarbaru; Balitra, Jalan Semeru (Semeru Street), Mandiangin Circuit, and Banjarbaru Asri Housing. There took soil samples in three points of every area. By the test, obtained the correlation between CBR and Cone End Resistance (qc) on Banjarbaru area: CBR = 0.0545 qc + 2.618 and the qc score is between 50 kg/cm2 to 300 kg/cm2.